Pengaruh Struktur Corporate Governance Dan Financial Indicators Terhadap Kondisi Financial Distress - Rian Rosita (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to determine the effect of the board of directors, managerial ownership, institutional ownership, audit committee size, liquidity, leverage and profitability on financial distress conditions. The population in this study are Manufacturing Companies listed on the IDX in 2016-2019. The sample in this study was obtained using a purposive sampling method conducted on Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) in 2016- 2019 and based on predetermined criteria, a sample of 14 manufacturing companies was obtained. The analytical method used is multiple linear regression analysis with SPSS version 25 application tools. The results of the t-test analysis on the board of directors show a negative and insignificant effect on financial distress conditions, managerial ownership shows a negative and insignificant effect on financial distress conditions. , the institutional ownership shows a negative and insignificant effect on financial distress conditions, the size of the audit committee shows a negative and insignificant effect on financial distress conditions, liquidity shows a negative and significant effect on financial distress conditions, leverage shows a positive and significant influence on financial distress conditions, and profitability shows a negative and insignificant effect on financial distress conditions in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX).